(untitled) (Research, Society and Development, 2022)
The estrous cycle is related to the reproduction of a female. However, some diseases directly interfere in the reproductive cycle, an example is the hydrometra, a disease in which occurs the deposition of aseptic and translucent fluid in the lumen of the uterus and that may indirectly interfere in the cyclicity and reproductivity of a female. Given the above, the objective of this integrative review was to identify alterations in organs of the reproductive tract of pet females that favor the development of a hydrometric condition. This is an integrative review of the literature. We selected 14 articles that reported or addressed the theme of hydrometra in pet females (bitches, cats and rabbits). After the selection of the articles, relevant clinical information that may influence the development of hydrometra was extracted. The main conditions related to hydrometra were found in the literature: ectopic location of ureters within the uterus wall and vagina; canine Gartner duct cyst with renal agenesis; urolithiasis; perineal and inguinal hernias; uterine aplasia; remnant ovary syndrome; adenoma and proliferative polyps in the endometrium; teratoma; uterine torsions and adenocarcinoma. Some authors report the importance of control in the use of exogenous progestins since the chronic stimulation of estrogen receptors in the uterine tissue may influence the increased production of intraluminal fluid. Finally, the importance of veterinary monitoring of animals in reproductive age and attitude for early diagnosis of disease and promotion of health and quality of life to females is highlighted.